Penerapan Terapi Diafragmatik Breathing Terhadap Penurunan Nyeri Pada Gastritis Melalui Aplikasi Teori Keperawatan Roy Adaptasi Model Di Wilayah Kerja Puskesmas Lubuk Durian - Mustika, Yulia; Handayani, Tita Septi; Susanti, Meri Efriana (Universitas Dehasen Bengkulu, 2025)
Gastritis is one of the ten most common diseases in hospital inpatients in Indonesia (Gustin, 2012). gastritis can cause a variety of symptoms, but the main symptom that is often complained of by gastritis patients is pain or discomfort centred on the upper abdomen. Diaphragm breathing exercise can be recommended as a nursing intervention and used as input (stimulus) in the adaptation process to reduce pain in gastritis. The general purpose of this case study is to apply the Roy Adaptation Model nursing theory to gastritis patients by performing and teaching Diaphragm breathing exercise to reduce pain intensity, this study was also conducted to determine whether the Roy Adaptation Model theory can be applied to gastritis patients by providing Diaphragm breathing exercise therapy. This case study method is a qualitative method with a Case study research strategy. by applying Adaptation nursing theory to patients suffering from gastritis. The results of nursing care in gastritis patients using Roy Adaptation Model nursing theory include: assessment of the adaptation system, analysis, diagnosis, nursing action, nursing implementation and nursing evaluation. Nursing problems found in patients are chronic pain (related to the inflammatory process). While the hypothesis and nursing interventions that are compiled are directed at helping to reduce pain intensity with Diaphragm breathing exercise therapy through the Model Adaptation System approach. This Roy Adaptation Model nursing model theory can be applied and applied well in nursing focusing on gastritis cases. Suggestions for health workers are for Diaphragm breathing exercise therapy in patients with gastritis to reduce pain intensity so as to improve mobilisation ability and reduce activity disorders due to uncontrolled pain.